Beyond the Numbers : Understanding the Institutions for Monitoring Poverty Reduction Strategies - Bedi, Tara (Washington, DC: World Bank, 2012)
This volume provides lessons on the design and functioning of such monitoring systems, based on the experience of twelve Poverty Reduction Strategy (PRS) countries (Albania, Bolivia, Guyana, Honduras, the Kyrgyz Republic, Malawi, Mali, Mauritania, Nicaragua, Niger, Tanzania, and Uganda). The focus is on the institutional arrangements of PRS monitoring systems - the rules and processes which bring the various actors and monitoring activities together in a coherent diagnostic tool - and a summary of the situation in these twelve PRS countries.